2021
DOI: 10.13057/biodiv/d220423
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and delineation of two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill: The leaf architecture approach

Abstract: Abstract. Antonio MA, Buot Jr. IE. 2021. Characterization and delineation of two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill: The leaf architecture approach. Biodiversitas 22: 1783-1789. The current taxonomic treatment for the wild and cultivated species of Dioscorea esculenta Lour. (Burkill) presented them as two different varieties. However, there are confusions among botanists and farmers. So, leaf architecture analysis was done to investigate whether leaf architecture data would support their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…& L.M.Perry) observed by Viacruciz and Buot (2021) include the laminar size, apex shape, base shape, areolation, and FEVs. It was also mentioned by Antonio and Buot (2021) that variations can be observed in the number of basal veins and 2° vein angle of divergence of the two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill.…”
Section: Delineation Of the Two Confusing Speciesmentioning
confidence: 91%
See 1 more Smart Citation
“…& L.M.Perry) observed by Viacruciz and Buot (2021) include the laminar size, apex shape, base shape, areolation, and FEVs. It was also mentioned by Antonio and Buot (2021) that variations can be observed in the number of basal veins and 2° vein angle of divergence of the two infraspecific taxa of Dioscorea esculenta (Lour.) Burkill.…”
Section: Delineation Of the Two Confusing Speciesmentioning
confidence: 91%
“…Specifically, this paper compared the shape, size and organization of their leaves including their leaf venation patterns. Several studies in the country have effectively demonstrated the value of using leaf architecture as tools for identifying and classifying plants, as well as in addressing taxonomic confusions (Villareal and Buot 2015;Jumawan and Buot 2016;Torrefiel and Buot 2017;Baltazar and Buot 2019;Paguntalan and Buot 2019;Hernandez et al 2020;Antonio and Buot 2021;Viacruciz and Buot 2021), and this is among the most valuable morpho-anatomical tools for species delineation (Masungsong et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…longaculeatus. In some leaf architecture studies, blade class was also used in delineating species in a particular genus and infraspecific taxa (Baroga and Buot 2014;Kpadehyea and Buot 2014;Tan and Buot 2018;Antonio and Buot 2021). In other economically important crops, like Glycine max, blade class was used as a tool in the identification of all accession of this species.…”
Section: Cucumis Melo Var Texanusmentioning
confidence: 99%
“…Dioscorea L. is the largest genus in the family Dioscoreaceae and accounts for more than 95% of the species in this family. It is estimated that the genus Dioscorea has about 600 species [11], which are distributed in Southeast Asia, Africa, Central America, South America, and other tropical or subtropical regions [9]. Although there are more than 600 species of Dioscorea, only a few are used as food, namely D. rotundata, D. cyaenensis, D. alata, D. dumetorum, and D. esculenta [10].…”
Section: Botany Of Dioscorea Esculentamentioning
confidence: 99%
“…Description of D. esculenta which has a climbing herb habitus (Figure 2A). Left twisted stem, and petiole prickly leaves, heart-shaped leaves (Figure 2B) and pubescent, spiked inflorescence with flowers having six petals and six stamens, some tubers covered with roots all over the surface, and white tuber flesh (Figure 1B) uniform [11]. Propagated by vegetative bulbi [10].…”
Section: Botany Of Dioscorea Esculentamentioning
confidence: 99%